Hiding in Plain Sight: The Globally Distributed Bacterial Candidate Phylum PAUC34f - Chen, Michael L.; Becraft, Eric D.; Pachiadaki, Maria; Brown, Julia M.; Jarett, Jessica K.; Gasol, Josep M.; Ravin, Nikolai V.; Moser, Duane P.; Nunoura, Takuro; Herndl, Gerhard J.; Woyke, Tanja; Stepanauskas, Ramunas (Frontiers in Microbiology, 2020)
Bacterial candidate phylum PAUC34f was originally discovered in marine sponges and are is widely considered to be composed of sponge symbionts. Here, we report 21 single amplified genomes (SAGs) of PAUC34f from a variety of environments, including the dark ocean, lake sediments and a continental aquifer. The diverse origins of the SAGs and the results of metagenome fragment recruitment suggest that some PAUC34f lineages represent relatively abundant, free-living cells in environments other than the sponge microbiomes, including the deep ocean. Both phylogenetic and biogeographic patterns, as well as genome content analyses suggest that PAUC34f associations with hosts evolved independently multiple times, while free-living lineages of PAUC34f also remain present in diverse environments.